(37) Mathematical Models in Operation Research النماذج الرياضية في بحوث العمليات - أ.د. محمد ابراهيم الدسوقي (معهد التخطيط القومي, 2026)
the content then moves to probabilistic models and stochastic processes, discussing replacement and renewal models for both gradually deteriorating and suddenly failing assets. It includes an in-depth analysis of queuing models, which aim to balance the cost of service with the cost of waiting. The research also covers inventory models for determining the economic order quantities and their timing to minimize overall costs. Finally, it delves into competitive processes, including game theory and bidding theory, to analyze optimal strategies in economic conflict environments. The document concludes with a review of sequencing models and supporting statistical techniques such as analysis of variance and correlation, emphasizing the comprehensiveness of operations research in addressing complex management and production problems تستعرض المذكرة تصنيف النماذج الرياضية المستخدمة في بحوث العمليات وتطبيقاتها العملية. تبدأ بتعريف النماذج البرمجية، مع تركيز خاص على البرمجة الخطية كأداة لتحقيق الاستخدام الأمثل للموارد المحدودة، مستعرضاً صياغتها الرياضية وطريقة "السمبلكس" في الحل، بالإضافة إلى حالات خاصة مثل نماذج النقل والتعيين والشبكات. ينتقل المحتوى بعد ذلك إلى النماذج الاحتمالية والعمليات العشوائية، حيث يناقش نماذج الإحلال والتجديد سواء للأصول التي تتهالك تدريجياً أو التي تتعطل فجأة، مع تحليل معمق لنماذج الصفوف (Queuing Models) التي تهدف إلى موازنة تكلفة الخدمة مع تكلفة الانتظار. كما يتناول البحث نماذج المخزون لتحديد الكميات الاقتصادية للطلب وتوقيتها بما يضمن تقليل التكاليف الإجمالية، وصولاً إلى العمليات التنافسية التي تشمل نظرية المباريات (Game Theory) ونظرية العطاءات (Bidding Theory) لتحليل الاستراتيجيات المثلى في بيئات الصراع الاقتصادي. ويختتم المستند باستعراض نماذج التتابع (Sequencing) والتقنيات الإحصائية المساعدة مثل تحليل التباين والارتباط، مؤكداً على شمولية منهج بحوث العمليات في معالجة المشكلات الإدارية والإنتاجية المعقدة .